2008
DOI: 10.1254/jphs.fp0071500
|View full text |Cite
|
Sign up to set email alerts
|

A Novel High Resolution In Vivo Digital Imaging System for the Evaluation of Experimental Cataract in Diabetic Rats

Abstract: Abstract. The purpose of this study was to establish a novel imaging system for evaluation of cataract in small animals. Diabetic cataract was induced in male Wistar rats by a combination of a bolus injection of streptozotocin (65 mg/kg, i.v.) and 5% D-glucose given as drinking water. To assess cataract development, we designed a digital camera system equipped with a nonreflecting illuminator for capturing clear high-resolution full lens images in the horizontal plane. Cataract was evaluated from the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…images of the whole lens of small animals and showed that the combination of streptozotocin treatment and D-glucose feeding was a useful procedure to minimize the variability and to shorten the period required for the development of diabetic cataract in rats (32). Using the digital camera system and the procedure, we found that nifedipine significantly slows the progression, but not the onset, of diabetic cataracts.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…images of the whole lens of small animals and showed that the combination of streptozotocin treatment and D-glucose feeding was a useful procedure to minimize the variability and to shorten the period required for the development of diabetic cataract in rats (32). Using the digital camera system and the procedure, we found that nifedipine significantly slows the progression, but not the onset, of diabetic cataracts.…”
Section: Discussionmentioning
confidence: 90%
“…Using the non-invasive and repeatable in vivo digital camera system designed for capturing full lens images of small animals, we assessed the effect of nifedipine and verapamil on the onset and progression of diabetic cataracts by comparing the severity of cataracts with two methods based on different principles (32). This work has been partly presented at the 114th Kanto Area Regional Meeting of The Japanese Pharmacological Society.…”
Section: +mentioning
confidence: 99%
See 3 more Smart Citations